Influence Of MWCNTs Addition On Mechanical And Thermal Behavior Of Epoxy/Kenaf Multi-Scale Nanocomposite - Mat Noor, Noraina Alia; Abd Razak, Jeefferie; Ismail, S.; Mohamad, N.; Yaakob, M. Y.; T. H., Theng (Institute Of Physics (IOP) Publishing, 2017)
This research was conducted to develop kenaf reinforced epoxy/MWCNTs multi-scale composite using kenaf fibre and MWCNTs as the reinforcement in epoxy as the hosted matrix. The composites were produced by using a combination of hand lay-up and vacuum bagging process. The selection of optimum composition of epoxy-MWCNTs is based on the MWCNTs loading and the resulted mixture viscosity. Lower resin viscosity is required to allow good wetting and interaction between matrix and filler, which will yielded superior final performance of the fabricated composites. Therefore, different loading of MWCNTs (0.0 wt. %, 0.5 wt. %, 1.0 wt. %, 3.0 wt. %, 5.0 wt. %, 7.0 wt. %) were used to investigate the mechanical and thermal properties of the composites. As a result, the epoxy/kenaf/MWCNTs multi-scale composite at 1.0 wt. % of MWCNTs addition had yielded substantial improvement by 15.54 % in tensile strength and 90.54 % in fracture toughness. Besides, the fracture surface morphology of the selected samples were analysed via scanning electron microscopy (SEM) observation to further support the reinforcement characteristic of epoxy/kenaf/MWCNTs multi-scale composite.